The efficacy of spinal anaesthesia with fentanyl supplementation for arthroscopic knee surgery: A meta-analysis of randomized controlled studies. (28th April 2020) - Chen, Jianfeng; Yan, Chao; Luo, Chaosong; Li, Guizhen; Yang, Zong
Introduction: The efficacy of spinal anaesthesia with fentanyl supplementation for arthroscopic knee surgery remains controversial. We conducted a systematic review and meta-analysis to explore the influence of fentanyl supplementation for arthroscopic knee surgery. Methods: We searched PubMed, Embase, Web of Science, EBSCO and Cochrane Library databases through May 2019 for randomized controlled trials (RCTs) assessing the efficacy and safety of fentanyl supplementation for arthroscopic knee surgery. This meta-analysis is performed using the random-effects model. Results: Five RCTs are included in the meta-analysis. Overall, compared with the control group for knee arthroscopy, fentanyl supplementation is associated with decreased time for sensory block regression to S1 (mean difference (MD) = −47.38; 95% confidence interval (CI) = −56.74 to −38.02; p < 0.00001), first ambulation (MD = −41.65; 95% CI = −65.11 to −18.19; p = 0.0005), first urination (MD = −23.45; 95% CI = −32.16 to −14.74; p < 0.00001) and hospital discharge (MD = −29.39; 95% CI = −44.73 to −14.06; p = 0.0002) but has no substantial influence on onset time of anaesthesia (MD = 0.50; 95% CI = −1.71 to 2.70; p = 0.66), duration for motor blockade (MD = −42.56; 95% CI = −119.18 to 34.07; p = 0.28), pruritus (risk ratio (RR) = 2.17; 95% CI = 0.28 to 16.90; p = 0.46) or nausea (RR = 0.42; 95% CI = 0.10 to 1.81; p = 0.25). Conclusions: Fentanyl supplementation benefits postoperative recovery after knee arthroscopy.